2007
DOI: 10.1590/s0034-72992007000200019
|View full text |Cite
|
Sign up to set email alerts
|

Participação do cerebelo no processamento auditivo

Abstract: The cerebellum, traditionally conceived as a controlling organ of motricity, it is today considered an all-important integration center for both sensitivity and coordination of the various phases of the cognitive process. Aim: This paper aims at gather and sort literature information on the cerebellum's role in the auditory perception. Methods: We have selected animal studies of both the physiology and the anatomy of the cerebellum auditory pathway, as well as papers on humans discussing several functions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…These studies pointed to a threshold reduction in cerebellar responses with the destruction of the inner ears of cats, demonstrating evidence of a pathway linking the cochlea to the cerebellum (38). Other authors have suggested, using evoked potential methods, that this peripheral afferent pathway tracks from the cochlear nucleus to the cerebellum (39). Animal studies also propose that cerebellar central afferent auditory pathways involve the pontine nucleus, inferior colliculus and auditory cortex (40), while the efferent auditory pathway track through the inferior colliculus, medial geniculate body and auditory cortex (41).…”
Section: Discussionmentioning
confidence: 93%
“…These studies pointed to a threshold reduction in cerebellar responses with the destruction of the inner ears of cats, demonstrating evidence of a pathway linking the cochlea to the cerebellum (38). Other authors have suggested, using evoked potential methods, that this peripheral afferent pathway tracks from the cochlear nucleus to the cerebellum (39). Animal studies also propose that cerebellar central afferent auditory pathways involve the pontine nucleus, inferior colliculus and auditory cortex (40), while the efferent auditory pathway track through the inferior colliculus, medial geniculate body and auditory cortex (41).…”
Section: Discussionmentioning
confidence: 93%
“…The activation of different cerebellar areas leads us to infer about a functional specificity of cerebellar areas, suggesting an analogy with computer functions, in which the cerebellum behaves as a computer which processes specialized data, integrating information from numerous origins and modes 8 . The great difficulty in finding patients with cerebellar lesions only made our study group very restrictive, including individuals with different cerebellar lesion etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of different cerebellar areas leads us to infer about a functional specificity of cerebellar areas, suggesting an analogy with computer functions, in which the cerebellum behaves as a computer which processes specialized data, integrating information from numerous origins and modes 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific regions in the lateral cerebellum in humans, particularly in the left Crus I area, are consistently activated in brain imaging studies involving auditory tasks ranging from passive listening to pure tones or clicks, to various types of active auditory discrimination of intensity, duration, location, pitch, timbre and speech (Petacchi et al, 2005; Callan et al, 2007; Sens and de Almeida, 2007; Wilson et al, 2009). Tasks involving temporal processing of auditory stimuli have shown that individuals with lateral cerebellar lesions could not accurately perceive the difference between ‘longer’ and ‘shorter’ acoustic tone bursts (Ivry et al, 1988), and cerebellar involvement in this task was later confirmed in normal individuals in a fMRI study by Mathiak et al (2004).…”
Section: The Cerebellum In Human Auditory Processingmentioning
confidence: 99%